2016
DOI: 10.1002/2016tc004248
|View full text |Cite
|
Sign up to set email alerts
|

Uplift rate transients at subduction margins due to earthquake clustering

Abstract: Coastal uplift is common in continental fore‐arc systems, with elevated paleoshorelines indicating that uplift rates can vary dramatically over time on individual margins. The origins of these changes in uplift rates are examined using a global data set of paleoshorelines together with 2‐D numerical models of subduction systems. Empirical paleoshoreline data (N = 282) from eight subduction margins indicate that uplift rates are generally not steady state and varied by up to a factor of 20 during the late Quate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 70 publications
1
53
0
Order By: Relevance
“…The EW faults are the longest at 19°S in the Rio Camarones drainage basin. Evidence for a temporal clustering of seismic activity (Mouslopoulou et al, ) and the occurrence of giant landslides at 19°S is suggested by previous work by Pinto et al () and Crosta et al (). The occurrence and concentration of mostly undated landslides could lead to the effect of 10 Be dissolution resulting in higher denudation rates in this setting.…”
Section: Discussionmentioning
confidence: 75%
“…The EW faults are the longest at 19°S in the Rio Camarones drainage basin. Evidence for a temporal clustering of seismic activity (Mouslopoulou et al, ) and the occurrence of giant landslides at 19°S is suggested by previous work by Pinto et al () and Crosta et al (). The occurrence and concentration of mostly undated landslides could lead to the effect of 10 Be dissolution resulting in higher denudation rates in this setting.…”
Section: Discussionmentioning
confidence: 75%
“…Marine terraces are also insightful markers for tracking coastal uplifts at intermediate timescales (i.e. 10 4 -10 6 years) with interpreted~10 4 -year-scale temporal variations proposed to relate to earthquake temporal clustering on upper-plate crustal faults 9 or cumulative megathrust earthquakes 8 . This transient signal is questioned by some authors that ascribe it to the uncertainty on age measurements of the terraces and to their .…”
Section: Discussionmentioning
confidence: 99%
“…anelastic) deformation. They include cumulative co-seismic slips on the subduction interface 7,8 and/or on forearc faults 9 and long-term aseismic processes, such as crustal deformation 10,11 and tectonic underplating [12][13][14][15][16] , both being partly driven by the frictional state of the underlying subduction interface 10,11,17,18 . However, the critical lack of constraints on the long-term (i.e.…”
mentioning
confidence: 99%
“…For instance, Melnick (2016) proposes that intermediate-depth earthquakes are responsible for the uplift of the northern Chilean coast while he discards the influence of interseismic fault locking. Other studies point to spatial relationships Geophysical Research Letters 10.1029/2019GL085377 between patterns of coupling coefficients and long-term features of the forearc in support of the influence of interseismic fault locking on topography building (Béjar-Pizarro et al, 2013;Mouslopoulou et al, 2016;Rousset et al, 2015;Saillard et al, 2017).…”
Section: Introductionmentioning
confidence: 98%